Communitarian educative proposal with robotics: evaluation and learning process outcomes - María Dolores Castro Rojas; Ana Lourdes Acuña Zuñiga (Ediciones Universidad de Salamanca, 2012)
<!--[if gte mso 9]> Normal.dotm 0 0 1 193 1102 Universidad de Salamanca 9 2 1353 12.0 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> The project seeks to expand young people´s educative horizons that live in conditions of poverty and social risk, by means of an innovative didactic proposal integrating robotics. In this way the participants design, construct and program prototypes in real situations giving them new ways to experiment and share a significant experience. Their building representations are constructed with mechanical LEGO bricks and controlled by iconographic language (Robolab 2, 9). In fact, it was developed in three communitarian centers, which are no formal centers of schooling, located in urban marginal communities. As part of the evaluative process it was observed that students might be much likely to work in groups to represent different environments or conventional events, integrating different mechanical systems to drive their robotics prototypes. Thus, students may incorporate automatic responses, as well as programming structures such as multitask, conditional loops, time control and use of sensors. For many young students of these communities there were over and over again constant social difficulties such as teamwork, lack of socialization skills and deficient formative experiences that we must pay attention to which ideas from our field do help these students build effective projects and significant robotics classroom. <!--EndFragment-->